Temperature modulates bimodal reproduction and energy allocation in the sea urchin Tripneustes gratilla - Liu, Zerui; Zhao, Xinye; Zhang, Jia; Guo, Yu; Yu, Gang; Ma, Zhenhua; Qin, Chuanxin (Frontiers in Animal Science, 2025)
Elucidating the gonadal development patterns of organisms holds significant reference value for advancing large-scale breeding and sustainable utilization of species. This study systematically investigated the annual population structure (test diameter-wet weight allometric model), gonadal histology (gametogenesis chronology), and environmental conditions of Tripneustes gratilla. The key findings include the following: 1. Test diameter (60.10–147.89 mm) exhibited a significant positive correlation with wet weight (R² = 73.54%), with both parameters peaking in May–June before declining sharply in September–October, indicating synchronized seasonal morphological changes. 2. Gonadal development displayed a bimodal pattern, with the gonad index (GI) reaching primary (8.26 ± 2.99) and secondary (7.30 ± 3.15) reproductive peaks in September and December, respectively. Compared with males, females presented significantly superior gonadal development during July–August (P < 0.05). 3. Water temperature dynamics were highly synchronized with GI fluctuations, where the July–September warming phase was strongly associated with reproductive peaks, confirming the temperature-driven physiological synchronization of reproductive cycles. These results demonstrate that T. gratilla employs dual survival strategies through seasonal adjustments in morphological-reproductive traits to adapt to environmental fluctuations, providing critical theoretical insights into the reproductive ecology of echinoderms.